Mappalelo Cakkuriri Ritual Ceremony Performance as Value Transmission Media (Catharsis, 2022)
Mappalelo Cakkuriri ritual ceremonies are a culture that has become a habit of the Puttada people from the past until now. This study aims to explain the performance of the Mappalelo Cakkuriri ritual ceremony as a medium for the inheritance of values ​​in the Puttada village community. The ritual ceremony is held every four years and, at the latest, every five years. The implementation of the ritual ceremony shows several series, including washing heirlooms, slaughtering buffalo, raising the Cakkuriri flag (Mappelelo Cakkuriri), and so on. The ceremony is a habit or culture with values ​​that are used as guidelines for the life of the Puttada community. It is a legacy of the predecessors passed down from generation to generation as a commemoration to be grateful, even as a method to overcome disasters. Mappalelo Cakkuriri ritual ceremony has its method of inheritance which is in line with education. The inheritance pattern in the ritual performance occurs genetically/vertical transmission (upright inheritance) from parents to their children and grandchildren. It applies to both the executors and the Puttada community in general. Then the educational process occurs in the Pappuangang Puttada organization, namely non-formal and informal education; in society, it occurs informally where the people are introduced to the Mappalelo Cakkuriri ritual performance since their childhood.